Save twilight selected poems - Cortázar, Julio 1914-1984 (Pocket poets series, 2016)
"World renowned as one of the masters of contemporary fiction, Julio Cortazar was also a prolific poet, who in his final months in Paris, ill with leukemia, assembled what he wanted saved of his life's work in verse. This expanded edition of Save Twilight, offers a bilingual survey of Cortazar's enduring poetry ranging through his various voices, moods, and styles"...